Implementasi Visualisasi Data Komoditas Pertanian sebagai Pendukung Penyajian Informasi di Yayasan Setara Jambi - Ade Maulana; Alan Kurniawan; Titania Aura Islamia; Siti Hafiza; Dadang Rahmadi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The presentation of clear and understandable information is an essential factor in supporting data management within an organization. Yayasan Setara Jambi, as an institution engaged in community empowerment and agriculture, requires well-structured agricultural commodity data presentation to ensure that information can be utilized effectively. This study aims to implement the visualization of agricultural commodity data to support information presentation at Yayasan Setara Jambi. The research employed a descriptive method with an implementation approach. The research stages included data collection, data processing using Microsoft Excel, visualization development in the form of charts, and information presentation based on the processed data. The data consisted of agricultural commodities, including oil palm, rubber, and food crops, collected from official data sources and adjusted to the organization's information needs. The results indicate that data visualization presents information in a more concise, systematic, and easily understandable manner compared to conventional tabular data presentation. Furthermore, the resulting visualizations facilitate the dissemination of information within the organization, making it easier to understand the condition of agricultural commodities based on the available data. Therefore, the implementation of agricultural commodity data visualization can support more effective information presentation at Yayasan Setara Jambi.